Secure vital indicators of air on board for passengers and crew - Запорожець, О.І.; Казанець, В.І. (Proceedings of National Aviation University (archive), 2009)
The analysis of harmful physical and chemical factors, which can negatively affect vital body indices of passengers and crew of airplane in the different conditions of flight is outlined in the article. On the basis of analysis the sanitary hygienically requirements conditions aboard an airplane are defined which do not contradict norms of flightworthiness of civil airplanes and guarantee safety of vital functions of crew and passengers.